The main causes and conditions of criminal offenses against the acquisition of rights to immovable property (Journal of actual problems of jurisprudence, 2023)
This article examines the current problems of a sovereign country, in particular, illegal encroachment on the right to own real estate. It raised questions about the main causes and conditions of criminal offenses. After all, the desire of the state, whose statuses are determined to exercise the rights of these persons, in realizing its main goal of ensuring their decent life, the competitiveness of the country is reflected in the country purposefully, professionally and effectively.Any legal state or state that is undergoing the process of its formation sets the goal of respecting the personality and freedom of every person and citizen, caring for disabled compatriots, honoring honest work, protecting mothers and children, family members, caring for pensioners, honoring veterans and defenders of the Fatherland, creating an independent and voluntary society.In many scientific studies, a step has been taken to analyze the basic principles of the organization and operation of the Kazakh system of ensuring human rights. These systems include such factors as the participation of the people as a source of state power, the ability to defend their rights.All of the above will make it possible to replenish the knowledge of comprehensive information about the formation and strengthening of the rule of law, the improvement of individual institutions that make up the supporting structures of State Independence, including on the implementation of constitutional human and civil rights.Keywords: acquisition of rights to immovable property, causes and conditions of offenses, state, personality, politics, law.